PERAN BIKKSA PCA LAMONGAN DALAM MEMBENTUK KELUARGA SAKINAH DI KECAMATAN LAMONGAN KABUPATEN LAMONGAN (ANALISIS UNDANG-UNDANG TENTANG PERKAWINAN) - Choiri, M. Qowi Indal; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2023)
This research is motivated by the increasing number of divorces in Lamongan Regency and the increasing number of requests for marriage dispensations. Therefore, a strategy is needed to overcome it. This study aims to find out the legal basis for the establishment of BIKKSA PCA Lamongan, to describe the forms of information and consultation carried out by BIKKSA PCA Lamongan in forming a sakinah family, and the role of BIKKSA PCA Lamongan in forming a sakinah family in accordance with the Law on Marriage. This study uses a qualitative approach, with data sources from the Chairperson and a member of the BIKKSA Branch Manager 'Aisyiyah Lamongan. Data collection techniques in this study were in-depth interviews, observation, and documentation. To analyze the data, the researcher used qualitative descriptive data analysis, namely describing data obtained directly in the field, then analyzing it based on data sources obtained from the literature, then arranged systematically to then be analyzed qualitatively into a description. The results of the study show that (1) the general legal basis for the establishment of BIKKSA is to intensify what is already in the legislation, and in particular, as a form of embodiment of the results of the 47th Mukatamar 'Aisyiyah in Makassar in 2015. (2) the form information and consultation that has been carried out by BIKKSA PCA Lamongan by running a socialization program for all PRAs as well as providing family coaching, distributing stickers to all PRAs, and having a breakthrough where the folding mat industry is made to support the economy as a form of business for realizing a sakinah family. (3) BIKKSA's role is in accordance with the contents of the Law on Marriage, both of them support the formation of a sakinah family, BIKKSA supports it through its role or practice, while the Law on Marriage supports it through its contents or in theory.